2020
DOI: 10.1590/1980-57642020dn14-040007
|View full text |Cite
|
Sign up to set email alerts
|

Social and health-related predictors of family function in older spousal caregivers: a cross-sectional study

Abstract: ABSTRACT. Given the benefits of adequate family function for the health and well-being of older adults, it is important to understand what factors predict adequate family function in older people who care for their spouses. Objective: Analyse predictors of family function in older spousal caregivers. Methods: A cross-sectional study design was used to investigate a non-probabilistic sample of 298 older spousal caregivers. Home-based face-to-face interviews were used to evaluate sociodemographic variables and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
2
7
0
4
Order By: Relevance
“…It was found that a greater depression level among the CDEP correlated with living with family members. This result is consistent with those of other studies [ 18 , 34 ]. The elderly who live with their families may still feel lonely because their families cannot meet their needs, which increases their isolation and depression [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…It was found that a greater depression level among the CDEP correlated with living with family members. This result is consistent with those of other studies [ 18 , 34 ]. The elderly who live with their families may still feel lonely because their families cannot meet their needs, which increases their isolation and depression [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…This emotional support received by the caregiver can work as an important tool for coping with stressful situations arising from care and causing intense burden (17) . The intensity of affection, the ability to adapt to an unexpected situation and to try to resolve it and companionship are fundamental for good family functionality, which is related to a high quality of life (8) . In addition, factors such as living in the same household as the older adults upon approval and intergenerational coexistence also influence the positive perception of family relationships (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies described the relationship between burden and family functionality, indicating that caregivers with low levels of family functionality had high levels of burden and perceived stress (6)(7)(8) . A study conducted in Italy with the objective of examine caregiver burden and its relationship with family functioning in different neurological conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os autores concluíram, ainda, que a melhoria do funcionamento familiar parece estar associada à recuperação do paciente com transtorno mental, pontuando que a avaliação familiar poderá ser uma metodologia adequada para a identificação dos fatores do ambiente familiar que podem auxiliar no planejamento terapêutico e na reabilitação do paciente psiquiátrico. Pavarini et al (2020) analisaram os preditores do funcionamento familiar em idosos cuidadores de cônjugues idosos, revelando que a presença de stresse, depressão, declínio cognitivo e número de filhos são preditores do funcionamento familiar e devem ser considerados no contexto da saúde geral do idoso. Num outro estudo, Ferriolli et al (2007) mostraram como variáveis do contexto familiar (e.g., stresse materno, instabilidade financeira) se associam a problemas de saúde mental da criança.…”
Section: Avaliação Do Funcionamento Familiar No Brasilunclassified